Women and the limitations of Zimbabwe’s indigenisation and economic empowerment policy: a gendered appraisal - Mudeka, Ireen (Booklove Publishers, 2017)
A book chapter by Dr Ireen Mudeka a Lecturer in the Development Studies Department, Midlands State University, Zimbabwe